The experiences of newly graduated nurses during their first year of practice in the Sultanate of Oman – A case study - Al Awaisi, Huda; Cooke, Hannah; Pryjmachuk, Steven (International journal of nursing studies, 2015)
Studies have demonstrated that the transition experience of new graduate nurses is complex and frequently negative, leading to dissatisfaction with nursing and increased attrition. Existing studies of new graduate nurses’ transition experiences tend to be concerned with the experiences of new graduate nurses in the West. To date, no study has been conducted examining the transition experience in any Middle Eastern country where the cultural context surrounding nursing education and practice is different. To explore the experiences of new graduate nurses during their transition period in the Sultanate of Oman. A qualitative case study utilising an embedded single case design was conducted to investigate the transition experience of new nursing graduates from one university in the Sultanate of Oman. Data were collected from the perspective of new graduate nurses and also from the perspective of other key informants who are key organisational actors such as clinical instructors, managers and preceptors. As is characteristic of case study design, this study employed triangulated methods including individual and focus group interviews, observation and documentary analysis. Data collected were thematically analysed using Microsoft Access. This study showed that nursing is not an attractive choice for Omani students to study and pursue as a future career. During the transition period, new graduate nurses experienced reality shock resulting mainly from a theory–practice gap. They found themselves with limited practical experience but a high level of theoretical knowledge that was difficult to utilise in practice. They experienced many competing priorities in their working environment which resulted in task-orientation and compromised patient care. Many new graduate nurses resented their involvement in basic nursing care, which they believed should not be part of their role as degree nurses. Omani new graduate nurses’ transition experiences are complex and highly affected by the working conditions and the status of nursing in Oman. Basic nursing care was believed by new graduate nurses to negatively affect the status of nursing.